Thriving amidst pandemic : the state of marketing commercial real estate leasing business - Manalansan, Carlo Ian A. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2022)
This Interpretative Phenomenological Analysis research study assessed the marketing management practices of the commercial real estate leasing owners/managers in the Province of Ilocos Sur amidst the COVID-19 pandemic. Interview questions were centered on the concepts of marketing management practices, challenges and/or problems encountered and industry development. The thematic analysis of the interviews resulted in four main themes: Implementing Ps of marketing, analyzing internal factors and external factors, receiving government support, and product management and provision on government support. The theme on implementing Ps of marketing embodies the following sub-themes: product, price, place and promotion. The theme on analyzing internal factors and external factors includes the different challenges or problems met by the commercial real estate leasing businesses which affect its operations. On the theme of receiving government support, it includes the support given by the government and other agencies. The theme product management and provision on government support comprises the measures employed by commercial real estate lessors in avoiding the challenges brought about by the COVID-19 pandemic, and sub-themes on the different needs of the commercial real estate leasing industry for government initiative. The functional relationship of these themes and sub-themes is demonstrated in the Thematic Model on Recovery and Growth of Commercial Real Estate Leasing Businesses, geared towards the recovery and growth through improved performance of commercial real estate leasing businesses in Ilocos Sur. In order to survive the challenges, the commercial real estate lessors focused on their product offerings and brand development amidst the challenges brought about by the pandemic. Commercial real estate lessors should consider adopting the recommended model on recovery and growth of commercial real estate leasing businesses.
References: pages 137-166.
CHED-La Union
Keywords: Real estate